Physicochemical composition of cookies added from red rice waste (Research, Society and Development, 2020)
The present article has as objective obtain the red rice residue flour (FRAV) and to apply in the elaboration a cookie type cookie, besides to characterize and to evaluate the effect of the addition of this flour on its physicochemical characteristics. The red rice residue was obtained in the extraction of the starch and was submitted to the drying process at 50 °C for 8h and characterized by the physicochemical and bioactive compounds parameters. The biscuits were prepared in 3 formulations (0, 50 and 100%) of red rice residue flour, and their physicochemical composition was determined. The red rice residue (FRAV) flour presented low moisture content and water activity, and also presented high levels of total phenolic compounds and antioxidant activity. The addition of the red rice residue flour in the elaboration of the cookies type cookies reduced the moisture, water activity, ash, lipids and pH values; and increase in protein, fiber and carbohydrate values presenting characteristics suitable for consumption.